Citra Merek, Inovasi Produk pada Minat Beli Ulang Es Krim di Sidoarjo - Ahcmady, Anggie Christian Nur; Wardhani, Nuruni Ika Kusuma (Mahesa Research Center, 2022)
This research examines the relationship between brand image and product innovation towards the desire to repurchase Campina ice cream in Sidoarjo Regency. Issues focused on brand image and product innovation within the Campina brand. The measuring instrument used is the brand image scale, product innovation scale, and repurchase intention scale for 100 Campina ice cream customers in Sidoarjo Regency. Quantitative analysis is conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the SmartPLS methodology. The results showed a significant positive effect between brand image and product innovation on the intention of repurchasing Campina ice cream in the Sidoarjo Regency. There was mean if the brand image and product innovation increase, repurchase intention will also increase. On the other hand, when the brand image and product innovation decrease, repurchase intention will also decrease. Repurchase intention is influenced by brand image and product innovation for 47.71%, whereas the remaining 52.29% is explained by variables outside the scope of this research (other than brand image and product innovation).